Determinant Analysis of Productivity on Rice Management in Indonesia (International Journal of Business, Economics and Management, 2019)
Farming management is done because management is the ability of farmers to plan, organize and control the factors of production that they control as well as they are and can provide the expected agricultural production. The measure of management success is the productivity of each factor as well as the productivity of his effort. The problem of the research is how the simultaneous and partial impact of labor variables, land area, farmer competency, the experience of farming, the role of government and farmer institutions to rice farming and how its performance through productivity analysis and R/C ratio. Primary data analysis using OLS multiple regression. The results of the analysis were obtained simultaneously that labor variables, land area, farmer competency, the experience of farming, the role of government and farmer institutions significant effect on productivity with a coefficient of determination of 56,9%. The farmer competency variable is the dominant factor that affecting productivity with a Beta value of 56,9%. R/C ratio value 1,90, it means that farming is done efficiently by farmers. Optimum productivity is achieved in farming with an area of more than 1 hectare. The research finding of this study is that farmer competency is a determinant of productivity in the management of rice farming.